Strengths and Dysfunctionalities of Formative Assessment: A Short Analysis from the Perspective of Romanian Education - Anghelache, Valerica (International Journal of Humanities and Social Science Research, 2015)
Evaluation reflects the educationalists’ interest in understanding and improving the techniques and instruments of school assessment. Postmodern didactics brings forth a fresh perspective on the evaluation act, which is analysed not only as the final act of the instruction process, but also as a process meant to permanently adjust teaching and learning acts. The aim of this paper is to underline the evolution of evaluation theory and practice in Romanian education, emphasising both its benefits and drawbacks. The paper uses the extant research in the literature as well as personal knowledge of the author about the factors that are related to the improvement of didactic evaluation. Most of the results of these studies lead to the conclusion that building a culture of evaluation is necessary, that formative evaluation should valorise a wide range of strategies and docimologic tools in order to attain an objective evaluation, and to be able to employ its outcomes in designing the teaching-learning undertaking.